Analisis Pengoptimalan Aplikasi Mobile dan Sosialisasi Unit CDC (Community Development Centre) guna Mempermudah Pengisian Form Dana Pinjaman UMK bagi Mitra Binaan PT Telkom Pematangsiantar - Alwi Akbar; Imsar Imsar (Universitas Muhammadiyah Metro, 2023)
This paper aims to determine the use of online applications at the CDC (Community Development Center) unit of PT Telekomunikasi Pematangsiantar. Based on the results of the analysis, the use of mobile applications as a medium to facilitate foster partners in filling out small and medium business loan funds forms. The mobile application is very effective in saving time, but there are some obstacles, namely the application often experiences errors. By optimizing the application, it is expected to be able to avoid these obstacles. Maximum utilization with an attractive appearance and ease of accessing applications that will increase the number of fostered partners in the CDC unit of PT Telekomunikasi Pematangsiantar.